Socio-economic characteristics of the fishing fleets operating in Benin, West Africa - Ahouansou Montcho, S; Gnansounou, Setondé Constant; CHADARE, FLORA JOSIANE; SALAKO, Kolawolé Valère; SOHOU, ZACHARIE; Failler, Pierre; GLÈLÈ KAKAÏ, Romain; ASSOGBADJO, ACHILLE EPHREM (My University, 2022)
The fishery industry plays a paramount role in poverty alleviation, food security and job creation in Sub-Saharan Africa. Scientific attempts to characterize the sector are however limited. This study used primary and secondary data from 2014 to 2018 to characterize fishing fleets and the diversity of fish species landed in Benin. Primary data were collected via face-to-face interviews and focus group discussions with informants identified using snowball and purposive sampling techniques. Secondary data on the landing statistics for five years (2014-2018) were additionally obtained from the Direction of Halieutic Production (DHP). Findings showed that five fishing fleets are currently operating in Benin, including the Artisanal National Continental Fleet (ANCF), Artisanal National Maritime Fleet (ANMF), Artisanal Foreign Maritime Fleet (AFMF), National Industrial Fleet (NIF) and Foreign Industrial Fleet (FIF). The mean annual volume from all the fishing fleets for the study period was 52,997 ± 12,269 tons, with an average commercial value of 82,194,096 ± 17,618,162 euros per year. Also, 48 species were recorded for the ANMF, 36 families of freshwater species for the ANCF, 43 species for AFMF, and 40 species for FIF. The catch volumes and their associated commercial values showed significant difference across the fishing fleets (ANOVA, p<0.05). This study highlights the paramount importance of the Artisanal National Continental Fleet in Benin and provides useful information for regional and global assessment of the fishery industry in the country.
Keywords: Fisheries; fleets; short-term assessment; West Africa.